Gender differences in postural balance, physical activity level, BMI, and body composition in athletes with visual impairment. (September 2022) - Esatbeyoglu, Ferhat; Kin-İsler, Ayse
The aim of this study was to examine the gender differences in postural balance, physical activity (PA), and body mass index (BMI) and body composition in visually impaired (VI) athletes. A total of 66 athletes took part in this study. After anthropometric measurements, the PA level was assessed by the International Physical Activity Questionnaire-Short Form. The modified Clinical Test of Sensory Integration and Balance tool was used to assess postural balance in four standing conditions: (1) eyes-open on a firm surface, (2) eyes-closed on a firm surface, (3) eyes-open on a compliant surface, and (4) eyes closed on a compliant surface. Findings revealed gender differences in anthropometric measurements ( p  < .05). No statistically significant differences were found in fat mass and fat free mass between sighted male and VI male athletes and between sighted female and VI female athletes ( p  > .05). Weekly, high and moderate PA levels as well as walking were found to be different across the four groups ( p  < .05). Assessment of postural balance in four standing conditions revealed no gender differences in sighted athletes ( p  > .05). Postural balance scores in conditions 1 and 3 showed significant gender differences ( p  < .05), whereas conditions 2 and 4 showed no gender differences in athletes with VI ( p  > .05). Gender-matched differences were also apparent in conditions 1 and 3, revealing that VI male and female athletes scored worse in these conditions than their sighted male and female counterparts ( p  < .05). There is a delay in balance parameter in VI athletes even if their fitness levels are similar with their sighted counterparts. The present findings could also be useful for gender-specific training session preparations in VI sports.